2011
DOI: 10.2528/pierc11072502
|View full text |Cite
|
Sign up to set email alerts
|

Self-Complementary Circular Disk Antenna for Uwb Applications

Abstract: Abstract-In this paper, the self-complementary principle has been applied to develop the traditional planar monopole antenna into a dipole antenna whose frequency range exceeds UWB requirements. The proposed design has compact, planar, and simple shape arranged in self-complementary manner connected to the (SMA) connector via rectangular microstrip line. The self-complementary structure offers better reduction of the imaginary part of antenna impedance, which allows matching on a wider band of frequencies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The input impedance of such type of antenna is generally characterized by its constant input impedance of 188.5 V. In spite of all the impressive aforementioned prospects, an additional impedance matching circuit is required to transform input impedance from 188.5 to 50 V in order to make it integrated with the RF front end [4][5][6][7]. In previous literatures, several types of self-complementary or quasi-self-complementary configuration have been explained for UWB application, such as half circular disk types [8], stepped triangular type [9], rectangular type [10], fractal BOW-TIE type [11], circular disk type [12], crossbar fractal type [13], horn-shaped self-complementary structure [14]. In this article, a novel design of microstrip line-fed quasi-selfcomplementary semi-octagonal band-notched UWB antenna is explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The input impedance of such type of antenna is generally characterized by its constant input impedance of 188.5 V. In spite of all the impressive aforementioned prospects, an additional impedance matching circuit is required to transform input impedance from 188.5 to 50 V in order to make it integrated with the RF front end [4][5][6][7]. In previous literatures, several types of self-complementary or quasi-self-complementary configuration have been explained for UWB application, such as half circular disk types [8], stepped triangular type [9], rectangular type [10], fractal BOW-TIE type [11], circular disk type [12], crossbar fractal type [13], horn-shaped self-complementary structure [14]. In this article, a novel design of microstrip line-fed quasi-selfcomplementary semi-octagonal band-notched UWB antenna is explained.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed design methodology is new in comparison to the previously reported work and our design is aimed to overcome the above drawbacks. Basic idea of semioctagonal self-complementary structure has been chosen as initial configuration due to its fairly compact size (26 × 36.6 mm) and simple shape compared with irregular and complicated shape (as discussed in previous literatures [2][3][4][5][6][7][8][9][10][11][12][13][14]). This kind of structure is able to reduce the influence of the discontinuity present in the antenna feeding point, which gradually changes the distribution of the current flowing from the feeding line to the radiant patch.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the notable studies found are that of [28][29] [30]. The authors in [31] have introduced triangular monopole, while authors in [32] and [33] have considered circular and elliptical monopoles Although the study have considered various technique to accomplish better bandwidth, but various extrinsic features like channel model, channel state, interference, and design principle of antenna was the major research challenge, which was not found much to be addressed. Certain studies [42] that have adopted planer monopole antenna are found to be frequently adopted by other studies too [43], [44].…”
Section: Existing Techniquesmentioning
confidence: 99%
“…Ultra-wideband (UWB) technique has drawn much attention for various applications [6][7][8][9]. A two-stage differential-mode BPF is designed using symmetrical bisections of branch-line topology [10].…”
Section: Introductionmentioning
confidence: 99%